INTRINSIC MOTIVATION OF STUDENTS DURING BLENDED LEARNING OF BUSINESS ENGLISH - Ogurtsova, Olga; Petrova, Svitlana (Continuing Professional Education: Theory and Practice, 2020)
The article discusses the issue of improving the efficiency of teaching Business English to students of economic specialties using educational Internet resources. The described method of blended learning involves the active independent work of students with resources hosted on the platform www.edx.org and active discussion of the results of this work during the classroom. The results of the survey indicate a high motivation of students to learning Business English according to the main principles of the blended learning approach. According to the survey conducted in the framework of the first stage of experimental research, during the work with the offered educational materials of the Internet, the intrinsic motivation of students was at a high level. In particular, the students themselves found such work useful and effective for developing competence in listening, reading, writing and speaking. Observation of the practical classes showed that students’ involvement in the educational process has increased significantly. Students ‘subjective feelings about the effectiveness of their online learning resources were supported by objective data, including the students’ performance charts, which were recorded by the platform. All students successfully completed more than half of the proposed assignments. Based on the results of the study, it can be argued that the use of edx massive open online courses in the framework of blended learning method (both in Ukrainian and in a foreign languages) in the teaching practice of higher educational establishments is very promising for improving the quality of education not only in Business English but also in other professional disciplines. Moreover, the use of edx massive open online courses in the framework of blended learning method will help students to develop continuing education tools and high intrinsic motivation to use these tools in their future professional and personal growth.